Ways of experiencing information literacy making the case for a relational approach - Andretta, Susie (Chandos Information Professional Series, 2012)
This book has two aims: firstly to present an investigation into information literacy by looking at how people engage with information to accomplish tasks or solve problems in personal, academic and professional contexts (also known as the relational approach). This view of information literacy illustrates a learner-centred perspective that will be of interest to educators who wish to go beyond the teaching of information skills. The second aim of this book is to illustrate how the relational approach can be used as an investigative framework. As a detailed account of a relational study, this book will appeal to researchers interested in using the relational framework to examine pedagogical experiences from the learner's perspective.--Publisher.